The smuggler - Plowright, Piers (London, United Kingdom: Macmillan Education, 2021)
Harker had written a poem before he was killed. But why? Harker wasn't a poet. He didn't even read poetry. He was a clever man, a tough man, but he was interested in money, not poetry. John Samuel Fame didn't understand it.
"British English"--Page 4 of cover.
Keywords: Police -- Fiction; Smuggling -- Fiction; Readers for new literates; Reading (Adult education); Readers (Adult); Readers for new literates; Detective and mystery stories